Simultaneous Determination of Sildenafil and Tadalafil in Legal Drugs, Illicit/Counterfeit Drugs, and Wastewater Samples by High-Performance Liquid Chromatography - Fidan, Ali Kemal; Bakirdere, Sezgin (AOAC INT, 2016)
A sensitive analytical method was developed for the simultaneous determination of sildenafil and tadalafil in legal drugs, illicit/counterfeit drugs, and wastewater samples. Chromatographic separation of two analytes was achieved on a C18 column with a mobile phase including 50 mM phosphate buffer at pH 6.0 and acetonitrile (35 + 65, v/v) at the flow rate of 1.0 mL/min. Analytes were separated from each other in 6 min with high resolution. LOD/LOQ values were calculated as 28/92 ng/mL for sildenafil citrate and 39/129 ng/mL for tadalafil. Calibration plots for both analytes were linear with correlation coefficients >0.9993. A validated method was successfully applied to legal and illicit erectile-dysfunction drug samples consumed in Istanbul, Turkey, and to wastewater samples. Nine different samples were analyzed for qualitative and quantitative measurement of their ingredients, and the results were compared with the values written on the labels of the drugs. The wastewater sample was also analyzed for its sildenafil and tadalafil content. To calculate the recoveries, a spiking experiment was performed and recovery rates for sildenafil and tadalafil were calculated as 101.30 +/- 3.43 and 102.68 +/- 1.59, respectively.
Keywords: TANDEM MASS-SPECTROMETRY; DIETARY-SUPPLEMENTS; STRUCTURAL ELUCIDATION; COUNTERFEIT MEDICINES; QUANTITATIVE-ANALYSIS; VARDENAFIL; INHIBITORS; ANALOGS; PHARMACEUTICALS; QUANTIFICATION; Chemistry; Food Science & Technology